Effects of Early Pulmonary Rehabilitation on Hospitalized Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis - Lu HY; Chen CF; Lee DL; Tsai YJ; Lin PC (International Journal of COPD, 2023)
Hsin- Yueh Lu,1,* Chiu-Fan Chen,2,3,* David Lin Lee,2,3 Yi-Ju Tsai,4 Pei-Chin Lin4,5 1Division of Respiratory Therapy, Department of Internal Medicine, Kaohsiung Veterans General Hospital, Kaohsiung, Taiwan; 2Division of Chest Medicine, Department of Internal Medicine, Kaohsiung Veterans General Hospital, Kaohsiung, Taiwan; 3School of Medicine, College of Medicine, National Yang Ming Chiao Tung University, Hsinchu City, Taiwan; 4Department of Medical Education and Research, Kaohsiung Veterans General Hospital, Kaohsiung, Taiwan; 5Department of Pharmacy, School of Pharmacy, Kaohsiung Medical University, Kaohsiung, Taiwan*These authors contributed equally to this workCorrespondence: Pei-Chin Lin, Department of Medical Education and Research, Kaohsiung Veterans General Hospital, No. 386, Dazhong 1st Road, Zuoying District, Kaohsiung, 813, Taiwan, Tel +886-7-3422121 ext 71584, Email pclin@vghks.gov.twBackground: Pulmonary rehabilitation (PR) effectively improves symptoms and exercise ability in patients with stable chronic obstructive pulmonary disease (COPD). However, the effectiveness and timing of early PR on hospitalized patients with acute exacerbation of COPD (AECOPD) is still debated.Methods: This study conducted a meta-analysis to compare the outcome benefits between early PR and usual care for patient hospitalized due to AECOPD. A systematic search was performed for retrieving randomized control trials (RCTs) from the PubMed, Embase, and Cochrane library until November 2021. RCTs reporting early PR for AECOPD with hospitalization, either during admission or within four weeks of discharge, were enrolled for systematic review and meta-analysis.Results: Twenty RCTs (1274 participants) were included. Early PR showed significantly improved readmission rate (ten trials, risk ratio 0.68, 95% confidence interval (CI) 0.50– 0.92), 6-minute walking distance (6MWD, twelve trials, MD 59.73, 95% CI 36.34– 83.12), St George’s Respiratory Questionnaire score (eight trials, MD − 10.65, 95% CI − 14.78 to − 6.52), Borg score (eight trials, MD − 0.79, 95% CI − 1.26 to − 0.32), and modified Medical Research Council dyspnea scale (eight trials, MD − 0.38, 95% CI − 0.5 to − 0.25). However, the trend of mortality (six trials, risk ratio 0.72, 95% CI 0.39– 1.34) benefit was not significant. The subgroup analysis showed non-significant trends of better effect in early PR during admission than those after discharge for outcomes of 6MWD, quality of life, and dyspnea. However, non-significant trends of less benefits on mortality and readmission rate were found in early PR during the admission.Conclusion: Overall, early PR is beneficial for AECOPD with hospitalization, and there was no significant outcome difference between PR initiated during admission or within 4 weeks of discharge.Keywords: chronic obstructive pulmonary disease, exacerbation, hospitalization, pulmonary rehabilitation